Avaliação e resolutividade do serviço odontológico no Sistema Único de Saúde - Lima, Arinilson Moreira Chaves [UNESP] (2015)
Community participation is an important tool for organizing actions and services of public health. The aim of this study was to determine the evaluation and the case-resolving capacity of dental care in the Unified Health System from the users' point of view, and their associations with humanization in care and access to oral health care, respectively. This research was part of a multi-centric study carried out in three municipalities in the midwest, southeast, and south of Brazil. It shows the results of the southeastern part of the larger project, carried out in Araçatuba, State of São Paulo. It was a cross-sectional survey-type research, with a quantitative approach, in which 461 users of the public dental service responded to individual interviews conducted in the health centers of the said municipality in São Paulo. Unified Health System users at or over the age 18, who agreed to participate in the study, and who, on the day of the interview, were undergoing or had completed dental treatment, were included. Users with special cognitive needs, and those who visited the said center for the first time were excluded. The questionnaire was adapted from the model used in the users' satisfaction survey of the National Health Service Evaluation Program, and from instruments of external evaluation of the Improvement Access and Quality National Program of Primary Health Care. For sample calculation, we used the prevalence of 50% for each possible condition in order to maximize the size of the sample. To the total found, 20% was added to leverage the effect of the study, reaching 461 individuals in the final sample. Chi-square and Fisher exact tests were used in bivariable analyses and Poisson regression, in the multivariable analysis. The dental care was positively evaluated by 90.4% of the participants. The negative evaluation of care was statistically...